KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (STUDI EMPIRIS PADA PEMERINTAH KOTA DEPOK TAHUN ANGGARAN 2015-2018 - Meyliana Adriani Lieubun; Ngadiman; Yustina Peniyanti Jap (Jurnal Kontemporer Akuntansi, 2022)
This research aimed to analyze the contribution of local taxes and regional levies on the local revenue of Depok city. The analytical method is a descriptive quantitative method, which analyzes target data and actual revenues of local taxes and retribution by using ratio analysis of the effectiveness and contribution. The results show that the level of effectiveness of local tax in 2015-2018 fiscal year tends to fluctuate and the level of effectiveness meets very effective criteria. The level of effectiveness of local user fees in the 2015-2018 fiscal year tends to fluctuate and the level of effectiveness meets very effective criteria except in 2018 it is not effective. Criteria for the contribution of local taxes in increasing local revenue is very good but the contribution of regional fees is very less.